Chinese herbal medicine Shenqi compound for early intervention in patients at high cardiovascular risk of type 2 diabetes mellitus: the protocol of a multicenter, randomized, double-blind, placebo-controlled trial - Leng, Yulin; Zhang, Zehua; Yao, Nairong; Fu, Xiaoxu; Xie, Hongyan; Gao, Hong; Xie, Chunguang (Frontiers in Cardiovascular Medicine, 2024)
Reducing multiple cardiovascular risk factors is a key link and a challenging clinical problem to reduce the risk of cardiovascular complications and death in patients with diabetes. Currently, there is a lack of clinical studies on patients with diabetes combined with multiple risk factors. Traditional Chinese medicine has therapeutic effects for comprehensive control of multiple cardiovascular factors. This study aims to provide evidence-based evidence for the efficacy and safety of Shenqi Compound (SQC) in early intervention of diabetic patients with high cardiovascular risk.This study is a multicenter, randomized, double-blind, placebo-controlled trial. 120 diabetic patients with high cardiovascular risk will be enrolled in five research centers. After a 2-week run-in period, the intervention group will receive basic treatment and SQC granules, and the control group will receive basic treatment and placebo granules for a total of 24 weeks, with a 24-week follow-up. The endpoint outcomes are major adverse cardiovascular events, renal-related and peripheral vascular disease events. The primary eEfficacy outcomes isare carotid intima-media thickness, and the secondary efficacy outcomes are carotid shear stress, indicators of glucose and lipid metabolism, pancreas islet function, hemorheology, traditional Chinese medicine syndrome score and quality of life scale. Safety indicators and adverse events will be used to assess the safety of SQC. This is a provisional file, not the final typeset article Discussion: This study comprehensively evaluated the efficacy and safety of SQC for early intervention in patients with diabetes at high cardiovascular risk from the aspects of overall metabolic level, structure and function of blood vessels, quality of life, and long-term follow-up of endpoint events, providing evidence-based evidence for the short-term efficacy and long-term benefits of early treatment to reduce the risk of diabetic cardiovascular complications.